Pericardial effusion in atrial fibrillation ablation: a comparison between cryoballoon and radiofrequency pulmonary vein isolation - Chierchia, Gian Battista; Capulzini, Lucio; Droogmans, Steven; Sorgente, Antonio; Sarkozy, Andrea; Müller-Burri, Andreas; Paparella, Gaetano; Carlo, de Asmundis; Yazaki, Yoshinao; Kerkhove, Dirk; Van Camp, Guy; Brugada, Pedro (Europace, 2010)
Aims Atrial fibrillation (AF) ablation is increasingly being performed in electrophysiology laboratories. Pericardial effusion (PE) is certainly one of the most frequently observed complications during AF ablation. The aim of our study was to investigate the incidence and outcome of PE following cryothermal energy balloon ablation (CBA) in comparison with conventional circumferential pulmonary vein isolation with a focal radiofrequency (RF) catheter. Methods and results A total of 133 consecutive patients (105 males) with paroxysmal AF were included in this study. Forty-six patients (36 males) underwent CBA (Arctic Front, Medtronic, USA) and 87 (69 males) point-by-point RF ablation guided by electroanatomical mapping (Carto, Biosense Webster, Diamond Bar, CA, USA). Ablation was performed under general anaesthesia with both techniques. All patients underwent a 2D transthoracic echocardiogram within 24 h before and after the procedure as routinely performed in our centre. Pericardial effusion was detected in 19 (14.2%) of 133 patients. Sixteen patients presented mild effusion, one moderate effusion, and two pericardial tamponades. There was no significant difference in the incidence of PE between the cryoballoon and the RF group (11 vs. 16%). A longer procedural time, coronary artery disease, and arterial hypertension were found to be independent predictors of PE during AF ablation. Conclusion Pericardial effusion occurred in a similar proportion following CBA and RF ablation for AF. Pericardial effusion was mostly mild and asymptomatic, with benign clinical outcome not requiring additional hospitalization days.